Who cares about local feed in local food products? Results from a consumer survey in Germany. Issue 3 (10th May 2019) - Profeta, Adriano; Hamm, Ulrich
Abstract : Purpose: The purpose of this paper is to analyse if German consumers are willing-to-pay a price premium for local food produced with local feed. The study provides insights into reasons explaining consumer preferences for animal products produced with local feed. Design/methodology/approach: Computer self-assisted personal interviews (CASI) with 1, 602 German consumers were conducted. To calculate the price premium for local feed, consumers were asked about their willingness-to-pay (WTP) for local feed. The respondents had to indicate their WTP for the local feed share levels 75, 90 and 100 per cent for pork cutlets, beef steaks, eggs and milk. To measure the impact of consumers' attitudes and sociodemographic background on the WTP, a zero-inflated negative binomial regression model (ZINB) was calculated. Findings: The study reveals that there is a high WTP for animal products produced with local feed. Furthermore, it delivers interesting insights into the WTP for different shares of local feed. Increasing WTPs for a 75, 90 and 100 per cent local feed origin could be found. The logit model in the zero-inflated regression showed that the buying frequency of organic foods exerted a particularly significant impact on one's belonging to the group which has, in general, no additional WTP for locally produced feed. Originality/value: Consumers' perception of the supply chain of local products is virtually unexplored. This is one of the first papers that take this topic into account.